Filsafat Akhlaq dalam Pemikiran Etika Kontemporer - Munawir Haris (Al-Riwayah : Jurnal Kependidikan, 2019)
In this modern age there have been many developments that have renewed the order of society in philosophizing including the way reacting to the morals philosophy. It soon becomes obvious that all sosial behaviors are developed out of the original trend. Basically, the ethical values of religion were from revelation, so the Islamic morals philosophy is not somewhat debatable point. Yet, this article puts forward the idea of Islamization of the philosophy of ethics by Muslims in the dynamics of the changing phenomena of the age. Some areas confirmed in this study are (1) problem formulation of the concepts or epistemology of ethics or morality; (2) the extend of developments and concepts of contemporary ethics; (3) position and response of the moral philosophy in contemporary ethical thinking. From some of the explanations and references, it can be concluded that morals are the manifest (outer)of behavior (verbal or deed) and the motivational encouragement of spiritual images (inner). However, terms of ethics relate to value system, a collection of principles or moral values (code of ethics), the knowledge of good or bad. By exploring the broad sources of ethics, it becomes clear that some problems with contemporary ethics appears in two levels namely global (sosial injustice, terrorism and threats, value-free action that sacrifices innocent people, ecological issues and sustainable development) and local level (high rate of corruption crimes, weakening the sense of humanity). As the morals philosophy falls into two major opinions (obedience to God's commands is subjective and the other is objective), the exploration in this occasion reflects the use of morals philosophy based on the normative understanding described in the Qur'an.